2019
DOI: 10.3368/jhr.56.4.0218-9363r2
|View full text |Cite
|
Sign up to set email alerts
|

Congestion Pricing, Air Pollution, and Children’s Health

Abstract: This study examines the effects of a congestion tax in central Stockholm on ambient air pollution and the health of local children. We demonstrate that the tax reduced ambient air pollution by 5-15 percent and the rate of acute asthma attacks among young children. We do not see corresponding changes in accidents or hospitalizations for nonrespiratory conditions. As the change in health was more gradual than the change in pollution, it may take time for the full health effects of changes in pollution to materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 16 publications
2
34
0
Order By: Relevance
“…Finally, our largest effects in percent terms are those on asthma visits by young children to emergency departments. The most closely related study in this regard is a recent working paper looking at the effect of congestion pricing in Stockholm (Simeonova et al, 2018). This study found that congestion pricing led to reductions in PM 2.5 of 15 to 20 percent and decreases in emergency department visits for young children of 12 to 47 percent (Simeonova et al, 2018).…”
Section: Discussion Of Magnitudesmentioning
confidence: 97%
“…Finally, our largest effects in percent terms are those on asthma visits by young children to emergency departments. The most closely related study in this regard is a recent working paper looking at the effect of congestion pricing in Stockholm (Simeonova et al, 2018). This study found that congestion pricing led to reductions in PM 2.5 of 15 to 20 percent and decreases in emergency department visits for young children of 12 to 47 percent (Simeonova et al, 2018).…”
Section: Discussion Of Magnitudesmentioning
confidence: 97%
“…Motivated by the "fetal origins hypothesis", a few papers investigate the persistent effects of early-life exposure to air pollution on economic outcomes such as human capital formation (Sanders 2012, Bharadwaj et al 2017) and labor market outcomes (Isen et al 2017) in the long-run. Relat-edly, Simeonova et al (2019) exploit the sequential introduction of Stockholm's congestion charge to demonstrate that health benefits increase with the duration of exposure to cleaner air. We add to this literature by presenting evidence for the persistence of health benefits from exposure to cleaner air in a fixed period of time, i.e., the period before age one.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence is deemed sufficient to conclude a causal relationship only in the case of the exacerbation of asthma. For recent quasi-experimental evidence of traffic-related pollution impacts on asthma, see Marcus (2017) and Simeonova et al (2018). 2 Anderson (forthcoming)-another related paper studying a relatively disadvantaged population-documents mortality impacts of car pollution for elderly Los Angeles residents living next to highways, exploiting the fact that downwind neighborhoods get more pollution on average.…”
Section: Introductionmentioning
confidence: 99%